Evolution of organ systems in the Crustacea: Mystacocarida and Cephalocarida in retrospect. Issue 2 (9th February 2019) - Elofsson, Rolf
Abstract: The morphology of the internal organs of two representative species of the crustacean classes Mystacocarida, Derocheilocaris typica (Pennak & Zinn, 1943 ), and Cephalocarida, Hutchinsoniella macracantha (Sanders, 1955 ), has been studied ultrastructurally from 1990 onwards. A review of the subject offers a unique opportunity to compare and contrast the two taxa at a time when their key positions in discussions of crustacean relationships and evolution makes any new knowledge particularly valuable. The same internal organ or organ system can be constructed very differently in the two groups, but similarities also occur. Both the similarities and differences suggest functional interpretations and shed light on evolutionary pathways. The importance of including anatomy and functional morphology in phylogenetic discussions is emphasized.